SIGN LANGUAGE TRAINING FOR HEALTH STAFF - Puguh Setyo Nugroho; Nyilo Purnami; Rosa Falerina; Rizka Fathoni Perdana; Yoga Rahmadiyanto; Hendra Kurnia Rakhma; Sumarman Sumarman; Sriati Sriati (Universitas Airlangga, 2022)
Effective communication is a pillar of excellent service in the healthcare unit. Communication among health workers, hearing impaired and speech impaired will cause obstacles to services. Sign language skills need to be possessed by health workers in communicating with people who are deaf and speech impaired. Socializing sign language and developing sign language skills for health workers in health services. After participating in the training, health workers are expected to know and have sign language skills. Community service activities in the form of sign language training for health workers in health services are carried out with lectures, quiz, discussions and practice of sign language skills. Activities are carried out through online method. The activity was attended by 1,593 participants. The most participants were midwives (570 participants-35.8%), nurses (518 participants -32.5%) and doctors (191 participants -12%). A total of 1,333 participants (83.7%) experienced communication problems with the hearing impaired and speech impaired. The training was felt to be useful by 1,215 participants (76.3%). The average result of the pre-test quiz was 33.54 (+13.11) and the average post-test quiz was 61.23 (+10.41). Comparison of pre-test and post-test results of hearing health education obtained statistically significant differences (p < 0.0001). The benefits of training activities are felt to be useful and needs to be intensified to improve the quality of services and the quality of life for people who are hearing impaired and speech impaired.